Snášenlivost a účinnost propiverinhydrochloridu u 752 pacientů s příznaky hyperaktivity detruzoru, zvýšené senzitivity a dráždivosti močového měchýře: výsledky studie sledování použití léku - Halaška, Michael; Voigt, R; Kaplan, F; Rauš, K; Mašata, Jaromír; Klemenc, J; Martan, Alois (Česká gynekologie, 1997)
In a post-marketing surveillance study of 752 patients suffering from urgent incontinence, mixed urgent-stress incontinence, reflex incontinence, urgency and enuresis were treated with propiverine hydrochloride. Clinical efficacy of propiyerine hydrochloride was verified by the improvement of symptoms related to detrusor hyperactivity, hypersensitivity and hyperreflexia miring a 12-week surveillance period: daytime and overnight urinary incontinence, as well as the frequency, nocturia, urgency in day time and at night decreased. These results are well demonstrated by decreased pad use and statistically significant decrease of Gaudenz urgency score during treatment, confirming the efficacy of propiverine hydrochloride already proved in clinical trials. The safety profile of propiverine hydrochloride displayed characteristic anticholinergic symptoms (dry mouth, accommodation disorders, constipation, tiredness, dizziness) with decreasing incidence during the 12-week treatment period. The residual urine volume decreased also. Serious adverse events were observed rarely and could be explained by the lack of consideration of contraindications, warnings and interactions with other drugs. The positive risk-benefit relationship of propiverine hydrochloride in the treatment of detrusor hyperactivity, hypersensitivity and hyperreflexia was reconfirmed in this post-marketing drug surveillance study.
Keywords: mužské pohlaví; Urinary Incontinence; benziláty; ženské pohlaví; Urinary Bladder; stresová inkontinence moči; Parasympatholytics; Humans; Urinary Incontinence, Stress; parasympatolytika; močový měchýř; Female; inkontinence moči; Benzilates; lidé; Male